Vztah české veřejnosti k Ukrajincům - Straková, Michaela (Lidé města, 2000)
A survey of the relationship of the Prague public to Ukrainians was conducted in a sample of one hundred respondents-Czechs aged 16 to 71 years. On the basis of this inquiry one can conclude that that part of respondents which has no experiences with Ukrainians, has assumed stereotype attitudes to them. By contrast, those respondents who really know Ukrainians, tend to have friendly relationships wíth them. In them they do not take into account the Ukrainians's nationality. An apathetic attitude to Ukrainians in the first stage of mutual contact in the Czech Republic has led into adopting two initial positions: either into a general perception of their attitude as "guest workers" or, in exceptional cases, as mafia criminals (especially under the influence of media coverage). Although after a several-year contact one cannot find hostility to Ukrainians among most respondents, one can still discern among them a certain reserve, typical of ethnically homogeneous societies.